2024
DOI: 10.3390/agriculture14020226
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Planting Years on Soil Physicochemical Indexes, Microbial Functional Diversity and Fruit Quality of Pear Trees

Xiaomin Pang,
Meihui Chen,
Pengyao Miao
et al.

Abstract: This study explores the interaction between pear fruit quality and the soil environment over four different planting years (5, 20, 30, and 40 years), focusing on the fruit’s chemical properties, rhizosphere soil properties, microbial communities, and both microbiomass and functional diversity. The results found that reducing sugar, sucrose, and vitamin C contents in pears initially increased with planting years before declining, while total acidity showed an inverse trend. Analysis of the soil physicochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…This study showed that rhizosphere soil microbial diversity of pear trees first increased and then decreased with increasing planting years (Figure 4). This is consistent with Pang et al (2024) results that the utilization rate of carbon source by rhizosphere soil microorganisms of pear trees also increases first and then decreases with increasing planting years. Bradyrhizobium is closely related to plant nitrogen fixation and can increase plant nitrogen fixation capacity (Akley et al, 2022).…”
Section: Figuresupporting
confidence: 92%
“…This study showed that rhizosphere soil microbial diversity of pear trees first increased and then decreased with increasing planting years (Figure 4). This is consistent with Pang et al (2024) results that the utilization rate of carbon source by rhizosphere soil microorganisms of pear trees also increases first and then decreases with increasing planting years. Bradyrhizobium is closely related to plant nitrogen fixation and can increase plant nitrogen fixation capacity (Akley et al, 2022).…”
Section: Figuresupporting
confidence: 92%